If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 35 = 15x + -17 Reorder the terms: 35 + 6x = 15x + -17 Reorder the terms: 35 + 6x = -17 + 15x Solving 35 + 6x = -17 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 35 + 6x + -15x = -17 + 15x + -15x Combine like terms: 6x + -15x = -9x 35 + -9x = -17 + 15x + -15x Combine like terms: 15x + -15x = 0 35 + -9x = -17 + 0 35 + -9x = -17 Add '-35' to each side of the equation. 35 + -35 + -9x = -17 + -35 Combine like terms: 35 + -35 = 0 0 + -9x = -17 + -35 -9x = -17 + -35 Combine like terms: -17 + -35 = -52 -9x = -52 Divide each side by '-9'. x = 5.777777778 Simplifying x = 5.777777778
| 5x+12y=60 | | 5/3k=10 | | -44=9p-8 | | -5x-4=66 | | j-3=-14 | | 2s+3t=13 | | (x+7)x+12=0 | | ax+5=6x+b | | A=24-(10-(20-a)) | | A=24-(10-(20-a)) | | 5(2x-3)=-105 | | 4y^2-y^2=10 | | 4y^2+y^2=10 | | y=(64)4x | | 3x-9=-15+2x | | B=10-(20-(24-b)) | | 12-21x+2x-6=-32 | | y=3x(48) | | (24-b)+(20-(24-b))=x-b | | x=2.5+1.5y | | -2x+y=-7 | | 31n=2(1.55n) | | -1/3x-3y=4/6x-1/3 | | (24-b)+b+(20-(24-b))= | | 50x(x^2-100)=0 | | 3p+15=36 | | 9x+1=36 | | 5n-8=-18 | | y=3(x)8+2(x)-9 | | 18c=90 | | y=4(x)7 | | x+5.7=8.3 |